Faculty of Business and Management is moving forward with IACCR international study visit expert forum sharing session - UiTM, Faculty of Business and Management (UiTM, 2023)
The Faculty of Business and Management (FBM) strengthened international collaboration through the IACCR International Study Visit Expert Forum Sharing Session, serving as a platform for knowledge exchange and global academic networking.